Manajemen Hubungan Masyarakat di SMP Negeri 7 Muaro Jambi - Armida; Riftiyanti Savitri; Erda (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to determine the management of public relations at SMPN 7 Muaro Jambi which focuses on planning, implementing and public relations obstacles at SMPN 7 Muaro Jambi. This research uses descriptive qualitative research methods. Data collection using interview, observation and documentation methods. The results of this study show that the planning carried out by SMPN 7 Muaro Jambi compiles a public relations program that will be implemented by involving all school parties. The implementation of public relations is carried out in accordance with the public relations program plan that has been prepared. The hindrance factor for the public relations of SMPN 7 Muaro Jambi is that there is no special field of public relations so that the duties and responsibilities are still managed by the principal and school administration.